Techniques for using VRChat to Replace On-site Experiments - Teo, Theophilus; Sakurada, Kuniharu; Fukuoka, Masaaki; Sugimoto, Maki (IEEE International Symposium on Mixed and Augmented Reality Workshops (Online), 2022)
In this paper, we present a technique to conduct on-site laboratory experiments using VRChat, a social Virtual Reality platform. COVID-19 pandemic has created challenges and restrictions on re-searchers in running experiments for Human-Computer Interaction research. Hence, universities and institutions set guidelines for social distancing and encourage people to work from home. Therefore, participants are harder to recruit for experiments that run in a physical laboratory. Our technique uses VRChat as a substitution for running on-site experiments despite social restrictions. We exploit features in VRChat to enable researchers to run experiments with domestically recruited participants. Furthermore, we propose a hassle-free method to retrieve study data. This paper also discusses and offers design considerations to run an on-site experiment using VRChat over a homemade system.